Breast Lumpectomy Surgery by Pectoral Nerve Block (Pecs Block) without General Anesthesia – A Case Report - Ida Bagus Reza Nanda Iswara; Wayan Widana (PT Dexa Medica, 2021)
Breast conserving surgery is usually performed under general anesthesia, or more recently combined with regional anesthesia techniques. Thoracic spinal block, thoracic epidural block, and thoracic paravertebral block are options of regional anesthesia that have been used in breast surgery, but anesthesiologists avoid them due to concern in potency of complications and side effects. After introduced by Blanco in 2011, pectoral nerves (Pecs) block appears as alternative procedure with fewer complications and lower incident of postoperative pain. In this case report we describe a 32-year-old female patient admitted for elective lumpectomy of the left upper quadrant of the breast. Ultrasound guided Pecs II block was chosen as the anesthetic technique for this patient. The authors reported succesful management of anesthesia and pain without complications in breast surgery. Pecs II block as single anesthetic technique can be considered safe, advantageous, and effective in breast surgery with good hemodinamic stability and few side effects.